Non-traditional security in Asia dilemmas in securitization - Anthony, Mely Caballero; Emmers, Ralf; Acharya, Amitav (Global security in a changing world, 2016)
The security issues confronting Asia are both complex and diverse. Given the increasing trend towards an expanding security agenda beyond the military dimension of inter-state relations, this volume provides an extensive study of emerging non-traditional challenges to this region. New realities and new challenges have come to the fore including environmental degradation, illegal immigration, infectious diseases, transnational crime, poverty and underdevelopment. Drawing upon the concepts of securitization and de-securitization, this book brings together regional perspectives from across Asia to examine how these challenges are perceived and managed. It is a valuable contribution to both security and Asian studies and will be ideally suited to those interested in security studies, international relations and development studies.